1999
DOI: 10.2307/3871046
|View full text |Cite
|
Sign up to set email alerts
|

Complete Sequence of the Mitochondrial DNA of the Red Alga Porphyra purpurea: Cyanobacterial Introns and Shared Ancestry of Red and Green Algae

Abstract: The mitochondrial DNA (mtDNA) of Porphyra purpurea, a circular-mapping genome of 36,753 bp, has been completely sequenced. A total of 57 densely packed genes has been identified, including the basic set typically found in animals and fungi, as well as seven genes characteristic of protist and plant mtDNAs and specifying ribosomal proteins and subunits of succinate:ubiquinone oxidoreductase. The mitochondrial large subunit rRNA gene contains two group II introns that are extraordinarily similar to those found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 84 publications
1
56
0
1
Order By: Relevance
“…1) are not significantly worse than the favored tree topology. This finding raises an important issue of a potential conflict between the CTDclade hypothesis and several recent phylogenetic studies that suggest red algae and green plants share a common ancestor (27,28). The evolutionary position of red algae has been debated for over a century and remains unresolved (17).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…1) are not significantly worse than the favored tree topology. This finding raises an important issue of a potential conflict between the CTDclade hypothesis and several recent phylogenetic studies that suggest red algae and green plants share a common ancestor (27,28). The evolutionary position of red algae has been debated for over a century and remains unresolved (17).…”
Section: Resultsmentioning
confidence: 93%
“…Based on these studies, and the cumulative results of many individual molecular phylogenetic investigations, the CTD-clade hypothesis is consistent with most reasonably well-supported relationships among eukaryotes. There is one possible exception to this generalization; that is a putative sister relationship between green plants and red algae that has been recovered in certain broad-scale phylogenetic investigations (27,28). Based on these analyses, it has been suggested that the results of RPB1 phylogenies, which consistently show independent origins for red algae and green plants, may be a phylogenetic artifact because of biases among RPB1 sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is not unexpected because the size of the commonly used genes is Ϸ300 positions, which provide little information to resolve such ancient events as the diversification of eukaryotes. It is thus not surprising that much recent progress has been based on the analysis of combined protein data sets (24,34,39).…”
mentioning
confidence: 99%
“…Because of the existence of an ␣-proteobacterial-type mitochondrial FtsZ (MtFtsZ) gene in red algae, which share a common ancestry with green algae and green plants (13,14), it is possible that higher plants have mitochondrial FtsZ genes in their genomes. But no ␣-proteobacterial-type FtsZ has been identified in the nuclear or mitochondrial genome of Arabidopsis thaliana (15,16).…”
mentioning
confidence: 99%